What to Say to Patrons About Buying Tickets Again? Modelling a Modern Relationship for Traditional Performing Arts. (November 2018) - Chang, Angela; Liu, Matthew Tingchi
Understanding patrons' repurchase intentions is a key area of focus for marketers, given its effect on survival and growth in competitive environments. Four types of relationships based on patron's satisfaction, product preference, product involvement, induced emotions and repurchasing intention were modelled to illustrate how current consumption influenced the repurchase intentions of performing arts patrons. An empirical study on an East Asian traditional culture performance from 671 patrons was conducted by using structural equation modelling (SEM) techniques. The result indicated that patrons' satisfaction was not the most direct determinant of their own repurchase intention, as initially theorized. Instead, patron preferences and involvement are the most proximal predictors of repurchase intent. Performing arts represent a leisure market sector that provides educational, entertainment and experiential services. Arts marketers can identify the factors that influence the patrons' repurchase responses to improve their' inherently experiential offerings. This study represents a sophisticated nature of the relationship with theatre patrons and offers theoretical and practical mediating attributes for arts marketing managers to consider in communication.